Trading of Ethnomedicinal Plants in the Indian Arid Zone - Kumar, Suresh; Parveen, F.; Goyal, S.; Chouhan, A. (Indian Forester, 2005)
Trading of ethno-medicillal plants in the Indian arid zone has been studied in the districts of Jaisalmer, Barmer, Bikaner and Jodhpur. Of 682 species reported in the Indian arid zone, 131 have been found to be of ethno-medieinal value. Of these, 41 species are collected and sold within Indian arid zone market. Large inter- and intra-district variation in sale prices was found. Of the top 20 species in domestic trade, 12 are from this area. Variation up to five times in their rate vis-a-vis western Rajasthan has been found. It has been concluded that 23 species can be prioritised for cultivation on large scale. Standardisation of product and price support are urgently required to promote herbal cultivation in western Rajasthan.